Pd loaded bismuth ferrite: a versatile perovskite for dual applications as acetone gas sensor and photocatalytic dye degradation of malachite green - Ghadage, Pandurang; Kodam, Pavan; Nadargi, Digambar; Patil, Suraj; Tamboli, Mohaseen; Bhandari, Nagesh; Mulla, Imtiaz; Park, Chinho; Suryavanshi, Sharad (Ceramics International, 2023)
Herein we report the palladium loaded bismuth ferrite for its bidirectional application as acetone gas sensor and photocatalytic dye degradation of malachite green. The motivation for loading Pd on bismuth ferrite (BFO) is due to its fascinating catalytic redox reactions causing faster adsorption and desorption of the oxygen molecules over the metal oxide. The planned perovskites were developed via surfactant assisted sol-gel auto-combustion route, and characterized their physico-chemical properties using XRD, SEM, TEM, HRTEM, EDAX, XPS and BET. The developed BFO showed the best selectivity towards acetone, whose response was 69% at 300 degrees C operating temperature for 500 ppm gas concentration. By tuning the surface area and catalytic behavior using CTAB and Pd loading, respectively, the enhancement in the gas response properties of BFO was achieved to 95% with the response and recovery time of 75 s and 104 s. The 1 wt% Pd loaded BFO showed the highest response (95%) in comparison to rest of the Pd loadings (0.5, 1.5 and 2.0 wt%). Moreover, the sunlight driven photocatalytic dye degradation of malachite green is carried out at 1 h exposure time. Here as well, 1 wt% Pd loaded BFO exhibited the maximum dye degradation efficiency of 51%. The results of this study demonstrate the developed perovskites have a significant potential for the use in dual applications such as acetone gas sensor and MG photocatalysis.
Keywords: Acetone sensor; Bismuth ferrite; Palladium loading; Photo dye -degradation